Therapeutic potential of anticoagulant therapy in association with cytokine storm inhibition in severe cases of COVID-19: A case report - Xu Qiancheng (De Gruyter, 2021)
Inflammation and coagulation are considered to the development of Coronavirus disease 2019 (COVID-19)-related hypoxemia. However, this is still controversial, which brings challenges to clinical treatment. Here, we reviewed the levels of interleukin-6 (IL-6), coagulation indexes, and clinical manifestations of a patient with severe COVID-19 after Tocilizumab administration. In this case, the patient’s body temperature quickly dropped to normal after using Tocilizumab, while C reactive protein progressively decreased and stabilized at a lower level. However, IL-6 and D-dimers increased and were accompanied by a continuous decrease of the oxygenation index. After anticoagulant therapy with heparin, D-dimer decreased slowly, gradually improving the oxygenation index and disease remission. This case suggests that the formation of microthrombus might be the main reason for COVID-19-derived hypoxemia. However, the mechanism of hypoxemia and the role of Tocilizumab in COVID-19 need further research. Nevertheless, these findings might still assist medical workers in formulating timely treatment strategies for similar severe patients.